(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Diabetes mellitus is among the most common disorder in developed and developing countries, and the disease is increasing rapidly in most parts of the world. It has been estimated that up to one-third of patients with diabetes mellitus use some form of complementary and alternative medicine. The medicinal plants refer to the plants extracts of different parts (leaves, seeds, roots, fruits etc.) which are used in the treatment of various diseases of humans, animals and plants. So, the study was carried out to ascertain the anti diabetic properties present in different extracts of dried scale leaves of Abrus precatorius. The present study is an attempt to highlight the anti diabetic activity as well as phytochemical and pharmacological reports on Abrus precatorius and calls for better-designed clinical trials to elucidate possible therapeutic effects on diabetes. The in-vivo studies on the chloroform leaves extract of Abrus precatorius revealed the presence of significant anti diabetic activity. Therefore, it can be used as a source of natural anti diabetic and used in drug formulations for treatment of diseases.